Pemahaman Guru Pendidikan Jasmani Olahraga dan Kesehatan Terhadap Pencegahan dan Pertolongan Pertama Pada Cedera Dalam Pembelajaran Penjas di SDN Se-Kecamatan Lamandau - widya, almaysi (Jurnal Keolahragaan JUARA, 2022)
Physical education learning is a subject that is more practical in the field. In the implementation of physical education learning, a student is very vulnerable to injury to the limbs. Therefore, injuries that occur during exercise should get more attention, by providing treatment for these injuries and prevention before doing sports in order to minimize the occurrence of injuries during exercise. Seeing this requires a good understanding by a physical education teacher to know and understand about prevention and first aid for sports injuries. Based on the results of qualitative research using observation, interviews, and documentation techniques carried out in 4 schools in Lamandau District, the results showed that the 4 teachers at SDN throughout Lamandau District were cognitively, affectively, and socially related to physical education teachers' understanding of prevention and treatment. First aid for sports injuries in physical education learning at SDN in Lamandau District is the main question of the researcher regarding understanding the definition of sports injuries, prevention of sports injuries, and first aid for sports injuries. The 4 teachers are very understanding. For a question that refers to the feelings/attitudes of the 4 teachers when a sports injury occurs. Mrs. Mido, 1 of the 4 teachers stated that when a sports injury occurred, they felt worried depending on the conditions at that time and 3 teachers stated that they always remained calm. For questions that lead to action, 4 teachers really understand what to do. The researcher concluded that the 4 teachers from 4 schools studied by the researchers, these teachers understood from their knowledge, feelings/attitudes, and actions taken.